Jellyfish Collagen: A Biocompatible Collagen Source for 3D Scaffold Fabrication and Enhanced Chondrogenicity - Lydia Powell (Marine Drugs, 2021)
Osteoarthritis (OA) is a multifactorial disease leading to degeneration of articular cartilage, causing morbidity in approximately 8.5 million of the UK population. As the dense extracellular matrix of articular cartilage is primarily composed of collagen, cartilage repair strategies have exploited the biocompatibility and mechanical strength of bovine and porcine collagen to produce robust scaffolds for procedures such as matrix-induced chondrocyte implantation (MACI). However, mammalian sourced collagens pose safety risks such as bovine spongiform encephalopathy, transmissible spongiform encephalopathy and possible transmission of viral vectors. This study characterised a non-mammalian jellyfish (Rhizostoma pulmo) collagen as an alternative, safer source in scaffold production for clinical use. Jellyfish collagen demonstrated comparable scaffold structural properties and stability when compared to mammalian collagen. Jellyfish collagen also displayed comparable immunogenic responses (platelet and leukocyte activation/cell death) and cytokine release profile in comparison to mammalian collagen in vitro. Further histological analysis of jellyfish collagen revealed bovine chondroprogenitor cell invasion and proliferation in the scaffold structures, where the scaffold supported enhanced chondrogenesis in the presence of TGFβ1. This study highlights the potential of jellyfish collagen as a safe and biocompatible biomaterial for both OA repair and further regenerative medicine applications.